Equinoterapia en niños con parálisis cerebral infantil - Tandalla Tipanluisa, Brayan Dario (2023)
ABSTRAC Equine therapy is a method of physical, psychological, social and cognitive rehabilitation that leads to improving the deficiencies of children with infantile cerebral palsy through stimulation. The process of the methodology that was used during the investigation, collection, analysis and description of the information obtained was of a documentary-bibliographic type with a qualitative approach, exploratory design and descriptive level, through the schematization of the information obtained from the different scientific bases. The 35 articles evaluated and analyzed with the PEDro scale determined that equine therapy is favorable in the recovery of children's abilities, due to the improvement of the physical, psychological, social and communicative condition during the development of the therapy that consisted of 1 to 2 sessions per week, for 30 to 45 minutes, performing better in daily activities. Keywords: Children, equine therapy, infantile cerebral palsy